2019
DOI: 10.3892/etm.2019.7265
|View full text |Cite
|
Sign up to set email alerts
|

BMP7 coordinates endometrial epithelial cell receptivity for blastocyst implantation through the endoglin pathway in cell lines and a mouse model

Abstract: Bone morphogenetic protein (BMP) expression has been observed in the uterus in previous studies. However, the influence of BMP7 on blastocyst implantation remains unclear. Blastocysts first act on luminal endometrial epithelial cells during implantation. The purpose of the present study was to explore the influence of BMP7 on endometrial epithelial cells. A pregnancy animal model, and mouse and human endometrial epithelial cells were used in the present study. Transient knockdown, immunofluorescence assay, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In our work, we focused on assessing the expression of BMP7 mRNA in the eutopic endometrium of women with endometriosis, confirming its significant upregulation compared to the control group. Other authors also showed increased expression of BMP7 , but before implantation, during the receptive period, compared with its baseline concentration in endometrial epithelial cells in mice [ 84 ]. Additionally, in the human endometrium, the expression of this gene was observed in cultured endometrial stromal cells with a high degree of decidualization [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our work, we focused on assessing the expression of BMP7 mRNA in the eutopic endometrium of women with endometriosis, confirming its significant upregulation compared to the control group. Other authors also showed increased expression of BMP7 , but before implantation, during the receptive period, compared with its baseline concentration in endometrial epithelial cells in mice [ 84 ]. Additionally, in the human endometrium, the expression of this gene was observed in cultured endometrial stromal cells with a high degree of decidualization [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within the wide range of mediators involved in the vascular process of early pregnancy, different authors have shown the importance of endoglin, von Willebrand factor and VEGF. Endoglin is expressed in the apical face of the luminal epithelium of the endometrium and the primary and secondary decidua in mice (Chadchan et al 2016, Yuan et al 2019. It has been shown that endoglin participates in the adhesion of the blastocyst to the uterus and modulates uterine receptivity during the window of implantation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, we observed an increase in endoglin expression at the implantation sites of females exposed to the EE. This increase might be related to the reception of signals released by the embryo (Chadchan et al 2016, Yuan et al 2019, which stimulate vascular remodeling of the maternal-fetal interface. On the other hand, the EE action on vascular remodeling seems not to be mediated by VEGFA or von Willebrand factor as we did not observe any differences between control and EE mice.…”
Section: Discussionmentioning
confidence: 99%
“…BMPs are shown to directly control endometrial receptivity via activin receptor type 2 A (ACVR2A) and SMAD1/5 signaling pathway (106,107). BMP7 is also involved in receptivity of the endometrium, regulating blastocyst implantation via the endoglin pathway (108). Upon implantation, BMP2 was shown to promote trophoblast cell invasion (109).…”
Section: Bmp In Patterning and Organoidsmentioning
confidence: 99%